Métricas e métodos para aprimoramento da produção sustentável: uma pesquisa-ação na indústria de materiais de fricção - Batista Junior, Orlando Henrique (Universidade Federal de São Carlos, 2022)
The concern of international bodies regarding sustainable consumption and production is growing due to the environmental impacts caused by humanity, and the constant governance of production processes is extremely important. In this context, this work proposes a sustainability indicator for monitoring and directions for the mitigation of environmental impacts caused in the production of friction materials, an industry highly harmful to the environment. For this, a research divided into four phases was carried out, in the first, a systematic review of the literature in international databases covering 1,573 articles. In the second phase, based on a deep content analysis, it was observed that the existing indicators, although they have general similarities, such as the evaluation of social, environmental and economic factors, lack external validity due to the singularities of the industries. indicator adapted to the industry studied. In the third phase, using the action research method for the application and practical validation of the indicator developed, identifying the critical points of the object of study. After applying operational research techniques and statistical analysis, according to phase four, important results were achieved, such as the reuse of 240 tons per year of materials previously considered waste, in addition, the decrease in the rate of harmful materials used in products fell from 24 .2% to 17.41%. In this way, the present work contributes to the refinement of the theory and the practical validation of sustainable metrics in the specific context of the friction materials industry, bringing to this context a tool for directing the improvement of this environmentally harmful industry.
Metrics and Methods to Improve Sustainable Production: An Action-Research in the Friction Materials Industry
Keywords: Indicador; TBL; Logística Reversa; Pesquisa Operacional; Indicator; Statistic; Reverse Logistic; Operational Research; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO